2020
DOI: 10.1128/jvi.00874-20
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycan Sites on the Influenza A Virus Neuraminidase Head Domain Are Required for Efficient Viral Incorporation and Replication

Abstract: N-linked glycans commonly contribute to secretory protein folding, sorting and signaling. For enveloped viruses such as the influenza A virus (IAV), the addition of large N-linked glycans can also prevent access to epitopes on the surface antigens hemagglutinin (HA or H) and neuraminidase (NA or N). Sequence analysis showed that in the NA head domain of H1N1 IAVs three N-linked glycosylation sites are conserved and that a fourth site is conserved in H3N2 IAVs. Variable sites are almost exclusive to H1N1 IAVs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…After BPL inactivation and purification, the viruses were adjusted to equal total protein concentrations and analysed. On both Coomassie stained SDS-PAGE gels (Fig 2C ) and immunoblots (Fig 2D), bands at the expected molecular weight of oxidized NA (dimers) and reduced NA (monomers) [19,36] were more apparent for WSN N1-BR18 than PR8 N1-BR18 , indicating WSN N1-BR18 virions incorporate more NA. The increase in NA levels correlated with a decrease in HA content but did not affect the HA processing to HA1 and HA2 or the content of the viral nucleoprotein (NP) or matrix (M1) protein (Fig 2C and 2E).…”
Section: Higher Na Activity Levels Correlate With Increased Na Virion Incorporationmentioning
confidence: 99%
See 2 more Smart Citations
“…After BPL inactivation and purification, the viruses were adjusted to equal total protein concentrations and analysed. On both Coomassie stained SDS-PAGE gels (Fig 2C ) and immunoblots (Fig 2D), bands at the expected molecular weight of oxidized NA (dimers) and reduced NA (monomers) [19,36] were more apparent for WSN N1-BR18 than PR8 N1-BR18 , indicating WSN N1-BR18 virions incorporate more NA. The increase in NA levels correlated with a decrease in HA content but did not affect the HA processing to HA1 and HA2 or the content of the viral nucleoprotein (NP) or matrix (M1) protein (Fig 2C and 2E).…”
Section: Higher Na Activity Levels Correlate With Increased Na Virion Incorporationmentioning
confidence: 99%
“…During previous studies, we observed that single-gene reassortant IAVs using NAs from subtype 1 (N1) are more easily rescued with a backbone from the A/WSN/1933 (WSN) strain compared to others and produce high NA levels [19,28,29]. To investigate this observation in a more controlled manner, single-gene reassortant IAVs carrying N1 antigens from the WHO recommended CVVs A/California/07/2009 (N1-CA09) or A/Brisbane/02/2018 (N1-BR18) were rescued using the seven gene segment backbone from WSN and PR8 (Fig 1A).…”
Section: Na Production By H1n1 Influenza Viruses In Mdck Cells and Eggs Is Strain Dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…During previous studies, we observed that single-gene reassortant IAVs using NAs from subtype 1 (N1) are more easily rescued with a backbone from the A/WSN/33 (WSN) strain compared to others and produce high NA levels [19, 28, 29]. To investigate this observation in a more controlled manner, single-gene reassortant IAVs carrying N1 antigens form the WHO recommended CVVs A/California/07/2009 (N1-CA09) or A/Brisbane/02/2018 (N1-BR18) were rescued using the seven gene segment backbone from WSN and PR8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C) and immunoblots (Fig. 2D), bands at the expected molecular weight of oxidized NA (dimers) and reduced NA (monomers) [19, 36] were more apparent for WSN N1-BR18 than PR8 N1-BR18 , indicating WSN N1-BR18 virions incorporate more NA. The increase in NA levels correlated with a decrease in HA content but did not affect the efficiency of HA processing to HA1 and HA2 or the content of the viral nucleoprotein (NP) or matrix (M1) protein (Figs.…”
Section: Resultsmentioning
confidence: 99%